TEKNOLOGI ROUGHING FILTER DALAM PENINGKATAN KUALITAS AIR PERMUKAAN DENGAN PARAMETER TOTAL SUSPENDED SOLIDS (TSS) TURBIDITAS DAN TOTAL COLIFORM (STUDI KASUS: AIR PERMUKAAN SUNGAI KARANG MUMUS) - Muhammad Busyairi (Universitas Mulawarman, 2018)
The high increase of population and economic activity of society. Community needs for clean water continue to increase. And with the limited capacity of clean water production by PDAM, it causes people to use other water sources. People who live on the banks of the river Karang Mumus use the river water without a treatment processing first. River polluted by suspended solids and also the presence of microbiological pollution requires natural processing, one of which is roughing filters. In this study we studied the decrease of total suspended solids, turbidity, and total coliform in raw water of Karang Mumus River by using roughing filter. And to know the effectiveness of gravel and brick media used as a medium of roughing filter. The medium used both pebbles and bricks, has three different sizes with the size of 12 – 18 mm, 12 – 8 mm, 4 – 8 mm. Roughing filter processing method used is upflow roughing filter in series with the addition of sedimentation basin at the beginning and slowsand filter at the end of processing. The results showed that roughing filter could decrease the total suspended solid parameter from 1450 mg/L to 200 mg/L on gravel media, and 1700 mg/L to 150 mg/L on brick media. In the turbidity parameter, gravel media can reduce turbidity from 729,33 NTU to 1,21 NTU, and on brick media turbidity value is lowered from 923,33 NTU to 2,19 NTU. And on total coliform from 35000 MPN/100 ml to 1600 MPN/100 ml on gravel media and from 17000 MPN/100 ml to 110 MPN/100 ml on brick media. There is no significantdifference in the efficiency by using gravel and brick media. But the brick medium is superior in decreasing the total suspended solids and total coliform parameters.